Naphthalimide-based conjugated macrocycles possessing tunable self-assembly and supramolecular binding behaviours - An, Dongyue; Sun, Yutao; Chang, Dongdong; Zhu, Jiangyu; Chen, Shumin; Lu, Xuefeng (Frontiers in Chemistry, 2022)
The special geometric configurations and optoelectronic properties of π-conjugated macrocycles have always been the focus of materials science. The incorporation of building moieties with different features into macrocycles can not only change their geometric configurations, but also realize the regulation of intramolecular charge transfer, which is expected to bring unusual performance in supramolecular chemistry and optoelectronic devices. Herein, four novel π-conjugated macrocycles based on typical electron acceptor units naphthalimide (NMI) with aryl or alkyl substitutions were reported. The different substitutions on NMI had greatly affected the self-assembly behaviours of these macrocycles. Alkyl substituted NP2b and NP3b showed obvious self-aggregation in solution, while similiar phenomenon was not found in aryl substituted macrocycles NP2a and NP3a, which can be attributed to the steric hindrance caused by rigid aryl groups that could affect the aggregation of macrocycles in solution. In addition, all the macrocycles exhibited supramolecular encapsulation with C70, in which the larger macrocycles NP3a and NP3b with twisted geometries showed stronger binding affinity towards C70 than the corresponding small-size macrocycles NP2a and NP2b with near-planar geometries. Our studies have greatly extended the family of macrocycles based on NMI, pointing out the direction for further supramolecular studies and applications on π-conjugated macrocycles.